2022
DOI: 10.3390/children10010050
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study to Measure Physical Activity with Accelerometry in ADHD Children according to Presentations

Abstract: (1) Background: Attention deficit hyperactivity disorder (ADHD) is a common mental disorder affecting 5–7% of school-aged children. Previous studies have looked at the effects of physical activity interventions on the symptoms of ADHD, although few have compared the motor behavior of children with ADHD versus those without. This exploratory study provides detailed information on the patterns and intensity of physical activity and sedentary behavior in children with ADHD as measured by Actigraph GT3X accelerome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Population-based studies of school-aged children and adolescents have found that youth with ADHD are significantly less likely to engage in physical activity and organized sports compared to peers without ADHD (Kim et al, 2011; Mercurio et al, 2021; Tandon et al, 2019). These findings may be driven by the inclusion of adolescents, as hyperactivity tends to decline with age (Willcutt et al, 2012), and research exclusively in younger samples supports higher levels of physical activity in children with ADHD compared to same-age peers measured via accelerometry (Villalba-Heredia et al 2022). There is also evidence from a longitudinal twin study that higher levels of physical activity is associated with reduced ADHD symptoms in adolescence, even after accounting for genetic and environmental confounding shared between identical twins (Rommel et al, 2015).…”
Section: Physical Activity In Adolescents With Adhdmentioning
confidence: 99%
“…Population-based studies of school-aged children and adolescents have found that youth with ADHD are significantly less likely to engage in physical activity and organized sports compared to peers without ADHD (Kim et al, 2011; Mercurio et al, 2021; Tandon et al, 2019). These findings may be driven by the inclusion of adolescents, as hyperactivity tends to decline with age (Willcutt et al, 2012), and research exclusively in younger samples supports higher levels of physical activity in children with ADHD compared to same-age peers measured via accelerometry (Villalba-Heredia et al 2022). There is also evidence from a longitudinal twin study that higher levels of physical activity is associated with reduced ADHD symptoms in adolescence, even after accounting for genetic and environmental confounding shared between identical twins (Rommel et al, 2015).…”
Section: Physical Activity In Adolescents With Adhdmentioning
confidence: 99%
“…There is preliminary evidence that a PA program may improve the cognitive functions and functioning of children with ADHD [23], including attention issues [24,25]. Additionally, PA impacts the mental health of children with ADHD [26], as they show poorer PAL compared to typically developing children [26,27]. Therefore, this study aims to (1) assess the PL level in children and adolescents with ADHD in Spain; and (2) improve PL and consequently HRQoL and ADHD symptomatology, including quality and sustained attention, through a PL program based on PA improvement, motivation, education and healthy lifestyle habits.…”
Section: Introductionmentioning
confidence: 99%